2019
DOI: 10.1186/s10195-018-0515-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing return to work after hip and knee arthroplasty

Abstract: BackgroundA substantial proportion of patients undergoing lower limb arthroplasty are of working age. This study aims to identify when patients return to work (RTW) and if they return to normal hours and duties, and to identify which factors influence postoperative RTW. The hypothesis is that there is no difference in time of RTW between the different types of surgery, and no difference in time of RTW based on the physical demands of the job.Materials and methodsConsecutive patients aged < 65 years who had und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 11 publications
4
29
0
Order By: Relevance
“…In this study, ICFS was used to assess fatigue. The results showed that the postoperative ICFS score of dexa group was (69.38±8.65), and was signi cantly lower than that of the placebo group [(78.94±10.34)], and the difference was statistically signi cant between the two groups (P=0.00), which was consistent with the ndings of McGonagle [20] and Whibley [21] .In addition, Lei et al [5] also supported our results.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, ICFS was used to assess fatigue. The results showed that the postoperative ICFS score of dexa group was (69.38±8.65), and was signi cantly lower than that of the placebo group [(78.94±10.34)], and the difference was statistically signi cant between the two groups (P=0.00), which was consistent with the ndings of McGonagle [20] and Whibley [21] .In addition, Lei et al [5] also supported our results.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, further analysis found that postoperative pain, nausea and fatigue may further increase patients' fear of discharge. Thus, it may prolong the hospital stay, which is consistent with the results of PEI et al [16] and McGonagle et al [20] , and it also indirectly con rms the systematic review of Whibley et al [21] .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…RTW was assessed using a standard patient survey. 28 Patients were first asked whether they were involved in paid employment within the 3-month period before surgery. If patients responded “yes,” they were instructed to submit the remainder of the survey.…”
Section: Methodsmentioning
confidence: 99%
“…Six studies found significant correlation while applying multivariate analysis. [11][12][13][14]18,19 Four studies did not perform any statistics but mentioned preferences or influencing factors reported by patients to be influencing their RTW. 9,10,16,17 Factors shown to be correlated with RTW by multivariate analysis were the physical nature of employment (p ¼ 0.03, 14 0.012, 11 and <0.0001 12,18 ), preoperative absence from work (p < 0.0001 18 and0.001 19 ), flexible work conditions Return to Work after Primary TKA at below 65 Years Van Leemput et al…”
Section: Associated Factorsmentioning
confidence: 99%